THE EFFECT OF SALES GROWTH AND COMPANY SIZE ON PROFITABILITY WITH COMPANY EFFICIENCY AS A MODERATOR - Novia; Ela Widasari; Siti Mudawanah (Politeknik Negeri Semarang, 2026)
This study examines the profitability of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the post-pandemic recovery period of 2021–2025. This study aims to analyze the effect of sales growth and company size on profitability, and examine the moderating role of company efficiency. This study uses an associative quantitative design with secondary data in the form of panel data from 21 companies selected through a purposive sampling technique. The data were analyzed using EViews 13 with Fixed Effects and Moderated Regression Analysis (MRA) models. The results show that sales growth has no significant effect on profitability, while company size has a positive and significant effect on profitability. Furthermore, company efficiency is unable to moderate the effect of sales growth or company size on profitability. These findings indicate that company scale is a key factor in determining profitability, while increasing sales without being accompanied by cost control does not guarantee improved financial performance.